Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
Franz Josef Fiord. SS Veslekari in Blomsterbukta, the only bay on western side of Ymer Island. In the background is Suess Land. Iceberg (left of ship) is one of largest we saw in this fiord.